A review of earthworm impact on soil function and ecosystem services. (21st February 2013) - Blouin, M.; Hodson, M. E.; Delgado, E. A.; Baker, G.; Brussaard, L.; Butt, K. R.; Dai, J.; Dendooven, L.; Peres, G.; Tondoh, J. E.; Cluzeau, D.; Brun, J.‐J.
Summary Biodiversity is responsible for the provision of many ecosystem services; human well‐being is based on these services, and consequently on biodiversity. In soil, earthworms represent the largest component of the animal biomass and are commonly termed 'ecosystem engineers'. This review considers the contribution of earthworms to ecosystem services through pedogenesis, development of soil structure, water regulation, nutrient cycling, primary production, climate regulation, pollution remediation and cultural services. Although there has been much research into the role of earthworms in soil ecology, this review demonstrates substantial gaps in our knowledge related in particular to difficulties in identifying the effects of species, land use and climate. The review aims to assist people involved in all aspects of land management, including conservation, agriculture, mining or other industries, to obtain a broad knowledge of earthworms and ecosystem services.